IMPLEMENTATION OF COMBINED PEST MANAGEMENT PERFORMS IN SERICULTURE – A CASE STUDY IN TIRUNELVELI DISTRICT, TAMIL NADU (International Journal of Food and Nutritional Sciences, 2022)
Sericulture is an agro-based initiative, highly suited to small and marginal farm holdings with less capital investment. Cocoon production involves activities namely, mulberry leaf production, which is the sole feed for silkworm and silkworm rearing. Both mulberry and silkworm are infested with a number of pests, which affect the cocoon quality and productivity resulting in economic loss to the farmers. Chemical control measure of pests is widely adopted by the farmers and its hazardous effects on human health and beneficial organisms are the least measured. Therefore, Integrated Pest Management (IPM) techniques mainly involving suitable biological measures have been evolved and popularized for the control of mulberry and silkworm pests. However, despite the favourable results, the adoption level has remained low. In this context, a study was conducted in Tirunelveli districts of Tamil Nadu with the information collected from 100 randomly selected farmers to understand the gap between available scientific knowledge in IPM practices and its implementation by sericulture farmers. The results revealed that there was the highest technological gap (89.60 %) in the adoption of biological control measures against the mulberry pests whereas the gap with cultural/ mechanical practices was 67.30 % and minimum 12.80% in the adoption of chemical measures. In case of management of Uzi fly threat on silkworms, there was no technological gap with respect to mechanical method of using nylon net to prevent the entry of Uzi fly inside the rearing house, whereas the technological gap of 87.00 % and 81.50% was observed for biological and chemical control methods, respectively. Thus, the IPM practices with the special emphasis on biocontrol method needs to be popularized among the farmers by intensified extension efforts for broaderimplementation at the farmer’s level.